Effectiveness of Manual Bronchial Clearance Techniques in the Treatment of Bronchiolitis - Nathali Carvajal-Tello; Alejandro Segura-Ordoñez; Valeria Grisales-Jaramillo; Laura Isabella Rayo-Salazar; Katheryne Julieh Hernandez-Peñuela; Jose Luis Estela-Zape (Life)
Background: Bronchiolitis is a seasonal viral infection of the respiratory tract that causes numerous childhood hospitalizations annually. Treatments vary based on severity, with mild cases requiring fluids and moderate to severe cases involving hospitalization with oxygen therapy, bronchodilators, and chest physiotherapy. Manual bronchial clearance techniques differ between Anglo-Saxon and European schools, and their effectiveness remains a subject of debate. Objective: The aim of this systematic review is to evaluate the effectiveness of manual bronchial clearance techniques in bronchiolitis by assessing clinical outcomes, including improved ventilation, increased oxygen saturation, and enhanced hemodynamic and respiratory stability. Materials and Methods: A systematic review was conducted between 2013 and 2024 using PRISMA guidelines. Databases searched included PubMed, Science Direct, Scopus, Springer, and Google Scholar; the inclusion criteria focused on randomized clinical trials and cohort studies in English, Spanish, and Portuguese. The selection bias was evaluated. The study was registered in Prospero (CRD42023486450). Results: Five articles involving 291 participants diagnosed with mild to moderate bronchiolitis were analyzed. The assessed techniques included Anglo-Saxon school and European School. Heart rate was evaluated in four studies, showing significant reductions in one (p < 0.01), while the significance in the other studies was not specified. Respiratory rate was assessed in three studies, with significant results being seen in two (p < 0.05). SpO2 was examined in all six studies, demonstrating significant improvements in two (p = 0.02 and p < 0.05). The Kristjansson respiratory score showed significant changes in one study (p = 0.005), and the Wang respiratory score indicated significant results in another (p = 0.03). These findings support the efficacy of chest physiotherapy techniques in managing bronchiolitis. Conclusions: While Anglo-Saxon techniques are widely used, their effectiveness remains a subject of debate. In contrast, European techniques indicate promising clinical outcomes, including improved ventilation, increased oxygen saturation, and enhanced respiratory stability; however, additional studies could further validate these findings.